Ginkgo biloba Extract Improves Insulin Signaling and Attenuates Inflammation in Retroperitoneal Adipose Tissue Depot of Obese Rats - Bruna Kelly Sousa Hirata; Renata Mancini Banin; Ana Paula Segantine Dornellas; Iracema Senna de Andrade; Juliane Costa Silva Zemdegs; Luciana Chagas Caperuto; Lila Missae Oyama; Eliane Beraldi Ribeiro; Monica Marques Telles (Hindawi Limited, 2015)
Due to the high incidence and severity of obesity and its related disorders, it is highly desirable to develop new strategies to treat or even to prevent its development. We have previously described that Ginkgo biloba extract (GbE) improved insulin resistance and reduced body weight gain of obese rats. In the present study we aimed to evaluate the effect of GbE on both inflammatory cascade and insulin signaling in retroperitoneal fat depot of diet-induced obese rats. Rats were fed with high fat diet for 2 months and thereafter treated for 14 days with 500 mg/kg of GbE. Rats were then euthanized and samples from retroperitoneal fat depot were used for western blotting, RT-PCR, and ELISA experiments. The GbE treatment promoted a significant reduction on both food/energy intake and body weight gain in comparison to the nontreated obese rats. In addition, a significant increase of both Adipo R1 and IL-10 gene expressions and IR and Akt phosphorylation was also observed, while NF-κB p65 phosphorylation and TNF-α levels were significantly reduced. Our data suggest that GbE might have potential as a therapy to treat obesity-related metabolic diseases, with special interest to treat obese subjects resistant to adhere to a nutritional education program.